Green HRM, Ethical Leadership and Sustainable Human Resources in International Organizations - Ernawati Ernawati; Abdul Kadir; Badrian Badrian; Naimah Naimah; Pati Matu Jahra; Nirsetyo Wahdi (Annals of Human Resource Management Research, 2026)
Purpose: This study examines how Green Human Resource Management (Green HRM), ethical leadership, psychological welfare, social inclusion, and corporate governance influence the implementation of Sustainable Human Resources (SHR) in international organizations, responding to the call for integrating environmental, social, and governance (ESG) principles into HR systems. Research Methodology: A cross-sectional, quantitative survey was conducted with 150 employees in international organizations involved in sustainability and ESG activities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test five hypotheses related to the influence of Green HRM, leadership ethics, welfare, inclusion, and governance on SHR. Results: The findings reveal that all five determinants positively and significantly affect SHR implementation. Green HRM and ethical leadership show the strongest effects, while psychological welfare, social inclusion, and corporate governance provide complementary contributions. The model explains a significant proportion of SHR variance, emphasizing the importance of integrating ESG practices within HR systems. Conclusions: This study highlights the need for a multidimensional approach to SHR, demonstrating that it emerges from the combined influence of Green HRM, leadership ethics, and governance practices, rather than isolated green or ethical efforts. Limitations: The use of non-probability sampling and cross-sectional data limits generalizability and causal inferences. Future research could employ longitudinal or multi-source designs across various contexts. Contributions: This study advances SHR literature by integrating five key constructs into a single framework and testing it in the context of international organizations, offering practical insights for HR leaders to design integrated ESG-focused HR policies.